Case of fatal air embolism during double-J ureteral stent placement - Peng Zhang; Chen Qing; Jianbo Li; Shisheng Zhu (Wolters Kluwer Medknow Publications, 2017)
Air embolism is a severe and fatal complication, but it is very rare during transurethral surgery. This report describes a case of air embolism during double-J ureteral stent placement in a 45-year-old woman. During ureteroscopy, a sudden decrease in oxygen saturation and end-expiratory carbon dioxide pressure and cyanosis of the face were observed. Subsequent echocardiography confirmed an air embolism by detecting bubbles in the heart. Despite resuscitative measures, the patient died rapidly. Detailed autopsy was performed to clarify the cause of death and the route of air entering into the circulatory system. The report presented here reminds urologists and pathologists that air embolism can occur during double-J ureteral stent placement and offers some suggestions regarding identification of air embolism at autopsy.